The beginning of the gospel: a theology of Mark - Orr, Peter (New Testament theology, 2023)
"This book seeks to explore the major themes of Mark's Gospel in the light of a wider biblical theology. Given that Mark was the first Gospel to be written, it is instructive to see the themes that he employs to connect Jesus to the wider story of the Bible. Many of these themes are raised in Mark and extensively developed in the rest of the NT, so carefully considering Mark's use of biblical theology is important to correctly orient us to the rest of the New Testament"--